Immunotherapeutic and pharmacological approaches for the treatment of Alzheimer's disease. (12th April 2018) - Moraes, Marcela Usmari; Gaudet, Timothy J
Abstract: The development of efficacious treatments targeting Alzheimer's disease (AD) aetiology has been proved an extensive, time-consuming task. Currently prescribed therapies, primarily acetylcholinesterase inhibitors such as donepezil and the NMDA-receptor antagonist memantine, concentrate on the improvement of symptoms such as cognitive decline and memory loss, however, do not address the underlying pathology of the condition. More recently, efforts have focused on developing drugs that target the hallmarks of AD, amyloid-β (Aβ) plaques and hyperphosphorylated tau tangles. Many clinical trials focusing on the removal of these proteins are presently ongoing, primarily exploring immunotherapeutic avenues such as the antibody aducanumab (targeting Aβ) and the vaccine AADvac-1 (targeting tau). However, the incomplete understanding of AD progression presents a challenge, and further studies focusing on the development of the disease are essential to the expansion of novel, efficient therapeutic routes.